2018
DOI: 10.1037/bul0000127
|View full text |Cite
|
Sign up to set email alerts
|

A social comparison theory meta-analysis 60+ years on.

Abstract: These meta-analyses of 60+ years of social comparison research focused on 2 issues: the choice of a comparison target (selection) and the effects of comparisons on self-evaluations, affect, and so forth (reaction). Selection studies offering 2 options (up or down) showed a strong preference (and no evidence of publication bias) for upward choices when there was no threat; there was no evidence for downward comparison as a dominant choice even when threatened. Selections became less differentiable when a latera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
480
7
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 510 publications
(523 citation statements)
references
References 95 publications
34
480
7
2
Order By: Relevance
“…The reference group in the study conducted by Ferrer-i-Carbonell contained individuals with (1) similar educational level, (2) similar age bracket, and (3) living in the same region. Beginning in 1954 when Festinger (1954) proposed this theory, there is also a longstanding tradition in investigating social comparisons (comparisons between the self and others) in social and personality psychology (Gerber, Wheeler, & Suls, 2018). According to that theory, social comparisons are an important psychological mechanism that affects the behaviour, experiences, and judgement of individuals.…”
Section: What Does This Study Add?mentioning
confidence: 99%
“…The reference group in the study conducted by Ferrer-i-Carbonell contained individuals with (1) similar educational level, (2) similar age bracket, and (3) living in the same region. Beginning in 1954 when Festinger (1954) proposed this theory, there is also a longstanding tradition in investigating social comparisons (comparisons between the self and others) in social and personality psychology (Gerber, Wheeler, & Suls, 2018). According to that theory, social comparisons are an important psychological mechanism that affects the behaviour, experiences, and judgement of individuals.…”
Section: What Does This Study Add?mentioning
confidence: 99%
“…Social comparison processes concerning the use of others as a comparison term for self-evaluation (Festinger, 1954) can play a role in evaluating decent work conditions. People tend to compare with others whether upward or downward in ranking dimensions (Gerber, Wheeler, & Suls, 2018). Comparisons are made of contents beyond those originally proposed by Festinger, i.e., abilities and opinions, and include life satisfaction, standard of living, wages, opportunities and others (Kruglanski & Mayseless, 1990).…”
Section: Decent Work: Integrating Cultural Complexitymentioning
confidence: 99%
“…Consumers have a fundamental motivation to attain status (Griskevicius & Kenrick, 2013), which leads them to be particularly attuned to how their own status compares to that of others (Corcoran, Crusius, & Mussweiler, 2011;Festinger, 1954). A recent meta-analysis showed that consumers predominantly tend to make upward comparisons (Gerber, Wheeler, & Suls, 2018), suggesting that consumers most often compare themselves to others who have more financial resources than they do.…”
Section: Introductionmentioning
confidence: 99%